Understanding Tourists’ Perceptions of Eastern Indonesia - Razak, Darmianti; Kesumah, Fajrin Satria Dwi (FEB - Universitas Lampung, 2019)
This paper examines tourists’ perceptions of Eastern Indonesia through comparisons with foreign visitors’ who have been to Indonesia, specifically Eastern Indonesia, and those who have never been to Indonesia. The aims of this study are to assess what foreign tourists perceive about Eastern Indonesia and elaborate the differences between the perceptions of visitors and non-visitors. The comparison of the visitor and non-visitor perceptions is important in order to understand Eastern Indonesia more deeply. This qualitative research uses focus group interviews to assess the perceptions of Eastern Indonesia. The perceptions from different participants came from different nationalities. In Group 1, two participants came from China, two Saudi Arabians, and one Bangladeshi. The four participants in Group 2 came from Australia. All of participants were students. The results indicate that tourists who have never been to Indonesia perceives Eastern Indonesia by comparing their experiences to other places that they have visited. From those experiences, they construct a positive image of Eastern Indonesia and as a result, indicate a willingness to visit Eastern Indonesia. All Australian participants had been to Indonesia and shared a positive image of Eastern Indonesia as well as of other places in Indonesia. However, while participants’ perceptions in Group 2 were positive, they also imply some ideas for the improvement regarding tourism development in Eastern Indonesia. Apart from that, all participants showed an intention to revisit and explore more places in EasternIndonesia in the near future.